A Refutation of the Hypothesis of the Superfidelity of Caricatures Relative to Photographs. (November 2013) - Hagen, Margaret A; Perkins, David
The experiment was designed to test the hypothesis that caricatures, relative to photographs, are 'superfaithful' carriers of information for facial recognition. Subjects were shown fifteen pictures of people's faces and were then asked to pick those same people out of a set of fifty-four pictures. There were three sets of pictures: caricatures, profile-view photographs, and three-quarter-view photographs. There were nine groups of subjects: for three groups the exposure and test stimuli were in the same medium, for six groups the test stimuli were in one of the media not previously seen. Points were scored for the number of people correctly identified and the number of false positives. Facial recognition within medium was very good, but was seriously disrupted by any medium shift, especially those involving caricatures. It is argued that the superfidelity of caricature may be manifest only when the task involves recognition of actual persons rather than their pictures.